Comparison of diagnostic scoring systems with imaging methods for the diagnosis of acute appendicitis - Birben, Birkan; Muge Sonmez, Bedriye; Er, Sadettin; Ozden, Sabri; Tugra Kosa, Murat; Tez, Mesut (Annals of Medical Research, 2021)
Aim: Acute appendicitis scores have been developed to better analyze the symptoms and signs of acute appendicitis. In this study, we compared the success rates of different scoring systems with imaging methods in the diagnostic confirmation of acute appendicitis.Materials and Methods: Patients aged above 18 years, who presented to the emergency department with right lower quadrant pain and were suspected to have acute appendicitis, were prospectively and observationally evaluated. The demographic characteristics, imaging modalities, Alvarado score, acute inflammatory response score, and adult appendicitis score were assessed.Results: 237 patients, 46.8% female and 53.2% male, mean age of 34±13 (18-95) years. Appendectomy was performed in 144 (61%) patients with a prediagnosis of acute appendicitis. The pathological results were appendiceal cancer in two patients, lymphoid hyperplasia in 12, and acute appendicitis in 130. Imaging methods were found to be more specific than scores, and positive predictive values in scoring systems were more sensitive than imaging methods in the diagnosis of acute appendicitis.Conclusion: There is still no effective and guiding scoring system for the diagnosis of acute appendicitis. Due to the low negative predictive values of the available scoring systems, patients should be evaluated with detailed anamnesis, examination and laboratory findings, and computed tomography should be performed if there is clinical suspicion of acute appendicitis.
Keywords: Acute inflammatory response score; adultappendicitis score; alvarado score; appendicitis; computed tomography